The Effect of Auditor’s Characteristics on the Future Stock Price Crash Risk - Faramarz Lotfi; Ali Akbar Ramezani; Seyedhossein Naslmousavi (Iranian Journal of Accounting, Auditing & Finance)
Negative skewness is among the features of crash risk that finally result in more volatility in the negative return. The contributing factors to stock price crash risk spread at the firm level, but the agency cost brings about information asymmetry. Should the information asymmetry between managers and investors be high, negative news about the firms would not transfer to the capital market on time, so when negative information holding passes the threshold, it will spread rapidly in the market and causes a drop in the stock price. According to the empirical observations, corporate governance is designed to decline agency cost and stock price crash risk. Hence, we can consider the auditors as a type of corporate governance effective in reducing agency costs and information asymmetry, so the objective of the present study is to assess the effect of auditor’s characteristics on future stock price crash risk. To reach the study's objective, 90 listed firms on the Tehran Stock Exchange were analyzed for 9 years from 2011 to 2019 using the descriptive-correlation analysis method and the multivariate regression test. The results of this study proved a significant and negative relationship between the auditor's characteristics ( such as consistency in the unqualified opinion and improved audit opinion) and the risk of the stock prices crash in the future. These findings reinforce the role of the audit report in evaluating the reliability of financial reporting and verifying that the auditor’s opinion impacts the market analysis. The results also show that the market can distinguish between the various types of auditors' opinions. Also, they show a negative and significant relationship between an auditor’s characteristics (the tenure of the auditor) and the risk of the characteristics stock prices crash in future. The empirical observations of this study are consistent with the supervised learning paradigm (theory). By showing that the auditors’ characteristics reduce the existing risk in financial markets, the present study contributes to the literature on determining factors in stock price crash risk and is the first study to assess the effect of improved and consistent qualified auditor’s opinion on future stock price crash risk.